PENGELOLAAN WAKAF ALKHAIRAAT PALU SULAWESI TENGAH - Lamuri, Ahmadan B. (Hunafa: Jurnal Studia Islamika, 2014)
Alkhairaat is one of institutions of education that possesses waqf institution. Nevertheless, the waqf institution is still managed traditionally, the lack of attention to the aspect of the development of the waqf institution, to that of standardization of its managers, to that aspect of the benefits and to that of the development of waqf property. As a result, the waqf institution administered do not possess driving force towards the economic development, the attractiveness of public trust, determinant force of economic management system as well as the competitiveness of the institution, both internally and externally. Based on the facts, it is suggested thatÂ  the Alkhairaat organization attempt to improve the managerial system of its waqf, paying attention to the essence of the waqf, and to establish the independence of its waqf institution in order to be able to implement good management.Kata kunci: Alkhairaat, pengelola wakaf (nÄáº“ir), manajemen.